Soccer coaches’ leadership styles and compatibility with youth players - Pedro Pugliesi Abdalla (2022)
It is important to analyze whether the way soccer players perceive the leadership of their coaches is related to the compatibility they assume about coaches. Studies on Brazilian soccer about this topic are still few in number. Thus, this study has three objectives: (a) analyze whether the compatibility between coaches and players differs depending on the coaches' leadership styles; (b) analyze whether the compatibility between coach and players differs depending on the closer approximation between the current and preferred behaviors of coaches perceived by players, and (c) analyze if players’ perception about the leadership styles of the coaches changes according to the age of the players. The evaluation protocol included the Multidimensional Scale of Leadership in Sport and the Coach-Athlete Compatibility Measure. One hundred and eighteen young players from five elite Brazilian football clubs participated in the study. Players who evaluated more positively the leadership styles of their coaches assumed higher compatibility with the coaches, and this result did not change according to the players’ age. In conclusion, the way players perceive their coaches' leadership is related to their compatibility with the coaches, being necessary to improve coaches’ leadership styles.